Diagnostic Relevance of Electromyographic Values and their Role in Forecasting the Conservative Treatment in Patients with Carpal Tunnel Syndrome - Haiko, O.G.; Klymchuk, L.I. (TERRA ORTHOPAEDICA, 2023)
Summary. Instrumental investigation and electromyography (EMG), one of the most widespread and informative of its methods, still remains widely used for differentiated diagnostics with any other disorder, compressive-ishemic focal neuropathy (CIFN) of the median nerve (MN) ) at the level of the carpal tunnel (CT) diagnosis verification and determination of the severity of damage to the MN. The clinical diagnosis of this pathologyis better know as carpal tunnel syndrome (CTS). Objective: To study the diagnostic relevance of electromyographic values in the Ukrainian population of CTS patients and their role in forecasting the efficiency of conservative treatment of this disorder. Materials and methods: 128 patients (204 extremities) with the clinical signs of CTS, who formed the Main Group (MG) underwent electromyography (EMG). The mean age of the patients was 58.2±12.5 years old; among them were 105 (82 %) women and 23 (18 %) men; 77 persons with a bilateral and 51 with a unilateral process. The control group (CG) included 30 volunteers (54 extremities) without any claims and signs of neurological symptoms. The mean age was 45.1±7.8 years old; among them were 23 (77.6%) women and 7 (23,3%) men. To determine the EMG predictors of the effectiveness of clinical outcomes after paraneural corticosteroid injection (PCI) 58 extremities MG were examined.For the EMG examination, we used the «Viking Quest» machine by Nicollet, the USA. Applying relevant methods, we investigated the following: median motor distal latency (DMLm) and CMAP of M. abductor pollicis brevis (APB); median sensory distal onset (MOL-D2), median sensory distal peak latency (MPL-D2), median SNAP amplitude digit 2, median sensory conduction velocity between wrist and digit 2 (mSNCV); difference in median sensory onset latency (digit 1) (MSL-D1) to radial sensory onset latency (digit 1) (RSL-D1) – MD1-RD1; difference in median nerve distal motor latency (2nd lumbrical)to the ulnar nerve distal motor latency (2nd interossei) – 2LI-DML; interrelation of the amplitudes of CMAP APB obtained by the stimulation of the MN on the level of the lower third of forearm to the amplitude of CMAP APB – on the level of the lower third of a palm (wrist to palm amplitude ratio); the sensory ulnar nerve conduction velocity (uSNCV). Results: The analysis of mean values of the core EMG values has demonstrated the significant differences between MG and CG, with different directions of changes, typical of the CTS. Relying on the data collected while studying people from the CG (the discovered referential and abnormal values) and the ROC analysis, we have established the sensitivity and specificity of EMG values: DMLm – 73.5% and 96.3%; MPL-D2 – 81.9% and 100%; mSNCV– 93.9% and 100%; MD1-RD1 – 62.5% and 100%; MSL-D1– 83.3% and 96.9%; 2LI-DML – 88.2% and 100%, respectively (AUC=0,91-0.96). Based on the results of the ROC analysis, determined that the most prognostically significant EMG predictor of clinical outcome after PCI was median SNAP amplitude digit 2 (sensitivity 90,9% and specificity 92%, AUC=0,95. Conclusions: The EMG is the objective and informative method to diagnose CIFN of the MN at the level of the CT, severity of nerve damage in CTS patients and predicting of clinical outcome after PCI.